2009
DOI: 10.1111/j.1365-2451.2009.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital imaging and public engagement in palaeontology

Abstract: Public engagement and the promotion of science to a wider non-academic audience form an integral role of the professional scientist in the twenty-first century. The high level of public interest in palaeontology means that the Earth's prehistoric past can provide an important medium through which to communicate information concerning contemporary scientific issues. Here we explain how modern computer techniques can be used to enhance public understanding of complex palaeontological issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 3 publications
0
20
0
6
Order By: Relevance
“…High-performance computing has become increasingly accessible to paleobiologists and provides the facility to rapidly solve the complex chain of equations that describe the mechanics and energetics of three-dimensional (3D) motion in jointed musculoskeletal systems. Computational methods are now standard for calculating the mass and inertial properties of organisms (Henderson, 1999;Henderson and Snively, 2004;Hutchinson et al, 2007;Bates et al, 2009aBates et al, , 2009b and for reconstructing the mechanical behavior (e.g., Rayfield, 2004Rayfield, , 2005Richmond et al, 2005), range of motion and functional repertoire (e.g., Stevens and Parrish, 1999), and likely kinematics and energetic performance of biological structures (e.g., Sellers et al, , 2005Nagano et al, 2005). These numerical analyses have some advantages over the more traditional methods of analogy and theoretical inference because they are inherently more objective and deterministic, producing explicit quantitative predictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-performance computing has become increasingly accessible to paleobiologists and provides the facility to rapidly solve the complex chain of equations that describe the mechanics and energetics of three-dimensional (3D) motion in jointed musculoskeletal systems. Computational methods are now standard for calculating the mass and inertial properties of organisms (Henderson, 1999;Henderson and Snively, 2004;Hutchinson et al, 2007;Bates et al, 2009aBates et al, , 2009b and for reconstructing the mechanical behavior (e.g., Rayfield, 2004Rayfield, , 2005Richmond et al, 2005), range of motion and functional repertoire (e.g., Stevens and Parrish, 1999), and likely kinematics and energetic performance of biological structures (e.g., Sellers et al, , 2005Nagano et al, 2005). These numerical analyses have some advantages over the more traditional methods of analogy and theoretical inference because they are inherently more objective and deterministic, producing explicit quantitative predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analysis on a volumetric reconstruction of the most complete specimen of Allosaurus currently known (MOR 693) indicates that the 'plausible' range for both total body mass values lies well within the range tested here for an Allosaurus with skeletal proportions similar to the model used here (Bates et al, 2009b). This study suggested that the trunk CM was likely to have been between 7% and 64% of femoral length cranial of the hip joint in Allosaurus (Bates et al, 2009b). Altering trunk CM across this range resulted in little change to maximum speed, but it did affect the kinematics of limbs and torso in running gaits owing to the sub-horizontal orientation of the torso in bipedal non-avian theropod dinosaurs.…”
mentioning
confidence: 99%
“…), se han ido incorporando de forma significativa al mundo de la Paleontología, primero a su ámbito científico, y en menor medida al educativo y divulgativo (Rahman, et al, 2012). En especial, los modelos digitales de fósiles adquieren mucha relevancia porque son muy eficaces para comunicar visualmente conceptos complejos o técnicos convirtiéndose en un recurso educativo transversal (Bates, et al 2009;Reynolds, 2010). El resultado de aplicar técnicas no destructivas (tomografía computerizada, escaneado láser o sincrotrón, etc.)…”
Section: Recurso Digitales 3d En Educaciónunclassified
“…También se usan para hacer reproducciones con fines museísticos (Falkingham, 2012), para estudiar sitios naturales de difícil acceso (Cayla, 2014), para la digitalización de yacimientos, como el caso de las icnitas de dinosaurios de Galve (Royo Torres, Mampel, & Alcalá, 2013), y en la gestión del patrimonio paleontológico como parte del geoturismo (Mallison, 2011;Gonzalez-Delgado, y otros, 2015). En el ámbito de la divulgación de la ciencia o en el educativo también son muy útiles los modelos 3D, permitiendo producir materiales didácticos que mejoran el aprendizaje en general (Bates, et al, 2009), y para los alumnos con deficiencias visuales, en particular, pues les permite tener acceso a fósiles que solo se pueden ver con lupa o en el microscopio (Teshima, 2010), ya que los modelos 3D se pueden ampliar y replicar a diferentes escalas.…”
unclassified
“…Digital approaches in palaeontology are an important medium through which to communicate information concerning contemporary scientific issues [Bates et al, 2009] and the goal of this project was to produce an interactive, educational exhibit featuring cutting edge computational techniques that could be used in the context of science festivals and other educational venues such as events at museums or school visits. We have been working for a number of years on the use of evolutionary robotics as a way of reconstructing the locomotor capabilities of fossil animals [Sellers et al, 2005;Sellers and Manning, 2007;Sellers et al, 2013] and have produced an open source simulation software package, GaitSym (http://www.animalsimulation.org) to do this.…”
Section: Introductionmentioning
confidence: 99%